2000
DOI: 10.1159/000018406
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Cutaneous Sarcoidosis: Search for Bacterial Agent by the 16S RNA Gene Analysis and Treatment with Antibiotics

Abstract: Background: The aetiology of sarcoidosis remains controversial. An infectious origin is often discussed, but only anti-inflammatory or immunosuppressive treatment is recommended. Objectives: To investigate the hypothesis of bacterial origin by treating cutaneous sarcoidosis with antibiotics. Methods: Patients with chronic cutaneous sarcoidosis, unresponsive to the usual treatment and not requiring systemic corticotherapy, were given combined antibiotherapy for 6 months. Search for bacterial DNA by amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Up to 60% of patients with sarcoidosis experience spontaneous resolution, and an additional 10–20% of patients show resolution of lesions with the use of systemic steroids [15]. Treatment with antibiotics is subject to controversy, especially since no evident bacterial origin could be demonstrated [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Up to 60% of patients with sarcoidosis experience spontaneous resolution, and an additional 10–20% of patients show resolution of lesions with the use of systemic steroids [15]. Treatment with antibiotics is subject to controversy, especially since no evident bacterial origin could be demonstrated [16]. …”
Section: Discussionmentioning
confidence: 99%
“…107,108 Other cases do not appear to be related to systemic sarcoidosis and may be a sarcoidal reaction to a foreign body. 126,127 The main candidate is a cell-wall-deficient form of an acid-fast bacillus, similar, if not identical to, Mycobacterium tuberculosis. The association in many of these conditions is probably fortuitous.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is important to consider that sarcoid granulomas constitute a chronic inflammation, rather than an acute inflammatory response and thus, even if microorganisms are the triggering factor, antibiotics could be ineffective due to the absence of an active infection within granulomas. Indeed, some studies have reported no clinical response in sarcoidosis patients treated with antibiotics [149].…”
Section: Main Textmentioning
confidence: 99%